A search for excited states of 3He by the reaction 7Li(d,6He)3He - Yu. N. Pavlenko; V. N. Dobrikov; N. L. Doroshko; V. O. Kyva; I. N. Kolomiets (Ядерна фізика та енергетика)
At deuteron energy of 37 MeV the 6 He inclusive spectra are measured in the exit channel of reaction 7 Li(d,6 He)3 He. The resonance-like structure of spectra in the range of 6 He energies corresponding to the excitation of 3 He recoil nuclei in the range of E* = 6…16 MeV was observed. The experimental data can be described in assumption of existence of 3 He resonances with excitation energies of Е* = 9, 13 and 16 МеV. An analysis of the experimental spectra shows that observed structure of 6 He spectra can be as well explained by the more probable processes of excitation and decay of 7 Li and 7 He unbound states in accompanied reaction channels.